096 COVID-19 in MS: clinically reported outcomes from the UK MS register. Issue 6 (27th May 2022) - Middleton, Rod; Craig, Elaine; Rodgers, William; Tuite-Dalton, Katie; Garjani, Afagh; Evangelou, Nikos; Hunter, Rachael; DasNair, Roshan; Nicholas, Richard
Abstract : Background: The UK MS Register (UKMSR) has been capturing longitudinal clinical and patient reported outcomes (PROs) since 2011. As the UK population 'locked-down' in March 2020 it became important that clinicians could record hospitalised MS patients due to COVID-19 and record outcome. The UKMSR provided an electronic case return form, designed collaboratively by the community. Aim: Impacts of disability, age and treatment on mortality in pwMS with COVID-19 Method: Linear modelling and standardised hypothesis testing were performed on an outcome of died or not, impact of disability (EDSS), disease modifying therapies and age. Results: N=132 PCR confirmed COVID-19 patients submitted, 14 missing EDSS, leaving n=118. Female n=80, n relapsing =74, n progressive = 44, mean age 49.2. Median EDSS = 5.0. Linear regression for age was found to be most significant for outcome (p=0.002). Univariate analysis found that the outcome was not independent of EDSS (ChiSq p=0.0008), DMT (ChiSq p=0.006) and MSType (ChiSq p=0.0006). In the multivariate model only, age remained significant. Conclusions: Only age remained as a marker of poor outcome multivariate analysis. No MS Specific characteristics were found to be significant. We would encourage continued data collection from UK neurology centres to increase the utility of this data. r.m.middleton@swansea.ac.uk 73